Upaya Guru Bimbingan dan Konseling dalam Menangani Siswa yang Kecanduan Game Online di SMPN 3 Kecamatan Harau Kabupaten Lima Puluh Kota - Dodi Pasila Putra; Deswalantri Deswalantri; Fadhillah Yusri; Tiara Afiah (Departement of Mathematics Education, 2023)
The purpose of this study was to find out what the guidance and counseling teacher's efforts are in dealing with students who are addicted to online games in students of SMPN 3 Harau District, Fifty City District. The purpose of this research is to add insight into the efforts of guidance and counseling teachers in dealing with students who are addicted to online games. This type of research is field research (Field Research) with a qualitative descriptive method, namely research that produces descriptive data in the form of written or spoken words from people and the observed behavior. The informants in this study were divided into two, namely key informants and supporting informants. Guidance and counseling teacher key informants, four student support informants. Data collection techniques used are observation, interviews and documentation. Based on the results of the study, it shows that the efforts of guidance and counseling teachers in dealing with students who are addicted to online games are using curative efforts. Curative effort is an activity or a series of treatment activities to overcome a problem that occurs. In curative efforts there is an alleviation function, where the alleviation function is an effort made to overcome problems through guidance and counseling services with the aim that deviant behavior does not occur again. Curative efforts are provided through basic services with individual counseling strategies, providing educational punishments to students and collaborating with related parties.